START WITH WHY : HOW GREAT LEADERS INSPIRE EVERYONE TO TAKE ACTION - Sinek, Simon (United Kingdom : Penguin Business, 2019)
Why do we do what we do? Why do we exist? Learning to ask these questions can unlock the secret to inspirational business. This title explains what it truly takes to lead and inspire and how you can learn how to do it.
Includes index
Includes bibliographical references
Keywords: Leadership; Leadership Psychological aspects; Business communication; Business and Management